A Perspective on Consumers 3.0: They Are Not Better Decision-Makers than Previous Generations - Houdek, Petr (Frontiers in Psychology, 2016)
This perspective article builds upon the theory of local thinking in interpretation and prediction of consumer behavior in a contemporary world of information overload. It is shown that even informed and socially and environmentally responsible consumers (consumers 3.0) exhibit selective recall, limited attention and bounded search in the perception and interpretation of price and quality of purchases. Their decisions fall into local cognitive frames, which specifically focus attention only on a narrow structure and content of the choice. The cognitive frames can be established by recent or regular purchases, but also extreme or primary purchase experiences. The article includes a short conceptual review of car, food, clothing, insurance, drugs, paintings and other product purchases showing that the local cognitive frames often lead to bad bargains across various sectors. The article presents several suggestions for future research.